Magnetic nanoparticle solid phase extraction-HPLC-UV for determination of deoxynivalenol in wheat flour. Issue 24 (19th November 2015) - Karami-Osboo, R.; Maham, M.; Mirabolfathy, M.
Abstract : Deoxynivalenol has been associated with human gastroenteritis and its presence in foods can cause clinical or subclinical manifestations in humans and animals. Abstract : Deoxynivalenol has been associated with human gastroenteritis and its presence in foods can cause clinical or subclinical manifestations in humans and animals. In this study, a fast, simple and validated extraction method of DON using Fe3 O4 magnetic nanoparticles (MNPs) was investigated and compared with an immunoaffinity column cleanup (IAC) process. The clean-up and extraction processes were merged in a single step by mixing MNPs, extraction solvents and wheat extracts. Possible impact parameters such as the amount of magnetic adsorbent, type and volume of extraction solvent, extraction time, salt addition and sample pH were investigated and optimized. Under the optimum conditions, DON was extracted and analyzed using high performance liquid chromatography with ultraviolet detection. The limits of detection (LOD) and quantification (LOQ) were 45 and 150 μg kg −1, respectively. The proposed method was applied to real wheat flour samples and also satisfactory recoveries were achieved by analyzing the spiked sample at concentration levels of 500, 1000, 1500 μg kg −1 ranging from 78.3 ± 5.4% to 93.8 ± 7.5%. The obtained results indicate that the proposed procedure could be used as an easy, rapid and economic method for extraction of DON in wheat samples.